Unveiling the Link between Stress Levels and Job Performance among Women in Nepal Banking Sector - Yadav, Indra (NPRC Journal of Multidisciplinary Research, 2024)
The banking sector in Nepal heavily relies on the contributions of female employees. However, concerns regarding the impact of stress levels on their job performance have emerged, given the industry’s high-pressure nature and cultural dynamics. This study aims to explore the relationship between stress levels and productivity, efficiency, job satisfaction, and retention rates among female banking professionals in Nepal. A comprehensive investigation was conducted using a Likert scale questionnaire distributed among female employees at Nepal Bank I. The questionnaire assessed various dimensions of job performance, including interpersonal, job, and organizational performance. Spearman correlation analysis and regression techniques were employed to analyze the data and test hypotheses regarding the influence of stress factors on job performance. The study revealed moderate to strong positive correlations between stress factors (job burnout, occupational stress, and psychological stress) and different dimensions of job performance. All nine hypotheses proposed in the study were confirmed, indicating a significant impact of stress on job performance. Regression analysis further supported these findings, highlighting the positive influence of psychological and occupational stresses on organizational and interpersonal performance. The findings underscore the importance of addressing stress factors in the workplace to enhance the well-being and effectiveness of female banking professionals in Nepal. By implementing organizational support and gender-sensitive policies, institutions can create a conducive work environment, leading to increased job satisfaction, productivity, and retention rates among female employees. This study contributes to the existing literature by providing empirical evidence of the relationship between stress levels and job performance specifically among female employees in the banking sector of Nepal. The confirmation of hypotheses and the identification of positive correlations between stress factors and job performance dimensions offer valuable insights for practitioners and policymakers aiming to promote the well-being and effectiveness of female professionals in the industry.